2021
DOI: 10.1002/stem.3329
|View full text |Cite
|
Sign up to set email alerts
|

The role of small extracellular vesicles in cerebral and myocardial ischemia—Molecular signals, treatment targets, and future clinical translation

Abstract: The heart and the brain mutually interact with each other, forming a functional axis that is disturbed under conditions of ischemia. Stem cell-derived extracellular vesicles (EVs)show great potential for the treatment of ischemic stroke and myocardial infarction. Due to heart-brain interactions, therapeutic actions of EVs in the brain and the heart cannot be regarded in an isolated way. Effects in each of the two organs reciprocally influence the outcome of the other. Stem cell-derived EVs modulate a large num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 120 publications
0
18
0
Order By: Relevance
“…Extracellular vesicles (EVs) are membrane particles secreted by most cells that constitute major vehicles for intercellular communication. In response to a stroke, EVs are released into the blood from brain cells and other organs [1][2][3][4][5]. These EVs can carry proteins and miRNAs that reveal important information regarding damage, protection, and the repair process after brain ischaemia, as well as stroke outcomes [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are membrane particles secreted by most cells that constitute major vehicles for intercellular communication. In response to a stroke, EVs are released into the blood from brain cells and other organs [1][2][3][4][5]. These EVs can carry proteins and miRNAs that reveal important information regarding damage, protection, and the repair process after brain ischaemia, as well as stroke outcomes [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The primary standard of ischemic stroke care is the delivery of tissue plasminogen activator (tPA); interestingly, the addition of exosomes to tPA treatment significantly improved functional outcome following stroke compared to tPA treatment alone [313,317]. Delivery of MSC-Exos in stroke models leads to long-term neuroprotection, improved neurogenesis and neurovascular remodeling, as well as enhanced behavioral and neurological performances in motor function, coordination, sensorimotor, and spatial learning [136,317,324,[326][327][328][329][330]. Varied contents of exosomes have been shown to aid recuperation, from growth factors such as VEGF to microRNAs [46,331].…”
Section: Brain Injurymentioning
confidence: 99%
“…Varied contents of exosomes have been shown to aid recuperation, from growth factors such as VEGF to microRNAs [46,331]. Zheng et al identified that miR-25 in MSC-Exos improved cell viability following stroke through modulation of BCL2/adenovirus E1B 19 kDa protein-interacting protein 3, while in a model of middle cerebral artery occlusion, miR-133b secreted from MSCs led to improved neurogenesis and stroke recovery [46,310,311,330]. Similar to studies in TBI, MSC-Exos can improve recovery through modulation of inflammation [43,136,310,313,328].…”
Section: Brain Injurymentioning
confidence: 99%
“…Cancer therapy [317] Exosomes from lung carcinoma cells [318] EVs from Staphylococcus aureus Intracellular delivery of antibiotics for intracellular pathogen-associated complications treatment [319] Exosomes from breast cancer Quantum dots of vanadium carbide Cancer photothermal therapy [320] Exosomes from hepatocellular carcinoma Silver and iron NCs Cancer bioimaging [321] Exosomes from macrophages SPIONs and curcumin Synergistic antitumor therapy in gliomas [322] Exosomes from plasma Superparamagnetic magnetite colloidal nanocrystal clusters Cancer treatment [323] EVs from KB cells Zinc oxide NCs Cancer treatment [324] Since EVs are remarkably involved in genetic information transfer in normal and pathological states [325][326][327], it is not difficult to see their potential as engineered nucleic acids carriers for drug the treatment of ischemic stroke, myocardial infarction [328], traumatic brain injuries [329], and liver fibrosis [330].…”
Section: Plga Npsmentioning
confidence: 99%